BIMBINGAN TEKNIS PENERAPAN PARTICIPATORY RURAL APPRAISAL DALAM PEMBERDAYAAN SUKU TALANG MAMAK DI KABUPATEN INDRAGIRI HULU - Siti Sofro Sidiq; Teguh Widodo; Seger Sugiyanto; Muhammad Faizal Dzulqarnain; Dian Kurnia Anggreta; Rufaidah Syafawani (Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
The purpose of this service is to provide technical guidance so that the process of formulating and implementing empowerment programs for the Talang Mamak Tribe can run according to the target. Participants in this service activity amounted to 30 people consisting of cross OPDs in Indragiri Hulu Regency as well as representation from the community and traditional leaders. The method of implementing activities with interactive lectures and question and answer discussions. Technical guidance activities for stakeholders in Indragiri Hulu Regency can run well. The Indragiri Hulu Regency Government, especially the Social Service, have been able to apply the principles of PRA in planning empowerment programs. Through PRA, the community is actively involved from problem identification, planning, to evaluation, so that the interventions designed are based on real needs and local wisdom. Collaboration between the Indragiri Hulu District Social Service, the Indonesian Ministry of Social Affairs and local institutions such as the Emak Sehat Institute strengthens holistic program implementation, avoids overlapping resources, and ensures effective coordination. Strategic partnerships become the main supporting pillar, where the role of facilitator institutions such as Emak Sehat bridges communication between the government and the community, while PRA-based technical training assists communities in data analysis and participatory planning. Recommendations from the follow-up of this service activity are to carry out capacity building training for the community.